Imaging the lower-crustal structures and precisely determining earthquake depth via advanced analysis of seismic later phases - Li, Tianjue (Nanyang Technological University, 2024)
Within the earth especially in the crust lie key minerals and energy resources, which are necessities to maintain modern industries/technologies. In addition, the earth’s crust preserves the oldest records of our planet’s evolution, holding the key to unlock insights into the early earth. The crust also imposes social challenges in the form of various natural hazards, e.g., earthquakes, tsunamis, and volcano eruptions. Thus, studies regarding the crust have long been the focus of geoscience society.